2004
DOI: 10.1021/jm049480l
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Evaluation of Pyridinic Analogues of Nimesulide as Cyclooxygenase-2 Selective Inhibitors

Abstract: In this study, we report the synthesis and pharmacological evaluation of original pyridinic sulfonamides related to nimesulide, a cyclooxygenase-2 (COX-2) preferential inhibitor widely used as an anti-inflammatory agent. These original pyridinic derivatives were synthesized in three steps starting from the condensation of 3-bromo-4-nitropyridine N-oxide with appropriately substituted phenols, thiophenols, or anilines followed by a reduction of the nitro moiety into the corresponding aminopyridine, which was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In addition to good anti-inflammatory, analgesic, anti-pyretic activities and low gastrointestinal toxicity, 1 is also useful in a wide range of disorders, which include various arthritic conditions, gynaecological and urological problems, post-surgical and cancer pain, and vascular diseases [3]. Several analogues of nimesulide (1) aimed at enhancing the antiinflammatory activity and reducing its toxicity have been reported by changing in 1 the R-group of the -NHSO 2 R moiety, the electron withdrawing group at the C-4 position and the central aryl ring by a pyridine or pyridinium moiety [4][5][6]. The X-ray structure analyses and molecular dynamics simulations of COX-2 complexes with nimesulide analogues indicate a network of hydrogen bonds in the COX-2 active site involving the nitrogen and oxygen atoms of the inhibitor molecule [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to good anti-inflammatory, analgesic, anti-pyretic activities and low gastrointestinal toxicity, 1 is also useful in a wide range of disorders, which include various arthritic conditions, gynaecological and urological problems, post-surgical and cancer pain, and vascular diseases [3]. Several analogues of nimesulide (1) aimed at enhancing the antiinflammatory activity and reducing its toxicity have been reported by changing in 1 the R-group of the -NHSO 2 R moiety, the electron withdrawing group at the C-4 position and the central aryl ring by a pyridine or pyridinium moiety [4][5][6]. The X-ray structure analyses and molecular dynamics simulations of COX-2 complexes with nimesulide analogues indicate a network of hydrogen bonds in the COX-2 active site involving the nitrogen and oxygen atoms of the inhibitor molecule [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…nitro by carboxy, ethoxycarbonyl, aminocarbonyl, cyano, aminosulfonyl or trifluoromethyl group and (iv) the central aryl ring by pyridine and pyridinium moiety. [14][15][16] All the members of this class of COX-2 inhibitors can be represented by a general structure 8 as shown in the Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore, became interested in attaching the EWG one atom away from the C-4 position and to study its subsequent effect on COX inhibition. Additionally, while the replacement of methyl group of NHSO 2 CH 3 of nimesulide by a trifluoromethyl (CF 3 ) moiety has been reported, 16 the role of acidic NH of methane sulfonamide moiety on anti-inflammatory activities, however, has not been studied extensively. Considering all these aspects and in continuation of our research on the development of novel anti-inflammatory agents we have prepared a number of chemically modified derivatives of nimesulide some of which showed interesting COX inhibiting properties.…”
Section: Introductionmentioning
confidence: 99%
“…The negative contribution of p para and sr shows that less hydrophobic and electron-donating para substituents at 2-phenyl ring (R1) play a crucial role in governing COX-2 inhibitory activity. Julemont et al [2004] reported a new series of pyridinic analogs of nimesulide (III) as selective COX-2 inhibitors. All the compounds together with the converted biological activity, pIC 50(COX-2) used for the analysis are given in Table 3 QSAR model 6 is a bi-parametric regression equation developed for COX-2 inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%